2022
DOI: 10.1155/2022/9386477
|View full text |Cite
|
Sign up to set email alerts
|

Association of PTPRT Mutations with Cancer Metastasis in Multiple Cancer Types

Abstract: Metastasis is one of the characteristics of advanced cancer and the primary cause of cancer-related deaths from cancer, but the mechanism underlying metastasis is unclear, and there is a lack of metastasis markers. PTPRT is a protein-coding gene involved in both signal transduction and cellular adhesion. It is also known as a tumor suppressor gene that inhibits cell malignant proliferation by inhibiting the STAT3 pathway. Recent studies have reported that PTPRT is involved in the early metastatic seeding of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…PTPRT , a member of the protein tyrosine phosphatase (PTP) family, has been reported to be a tumor suppressor gene in BC and other cancers. 38-44 NCKAP5 , potentially functioning in microtubule bundle formation and microtubule depolymerization, is less studied, and polymorphisms in this gene are reported to be associated with the clinical outcome of gastric cancer patients in a recent study. 45 Overall, our study suggests different genetic factors controlling tumor onset, multiplicity, metastasis, as well as the site of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…PTPRT , a member of the protein tyrosine phosphatase (PTP) family, has been reported to be a tumor suppressor gene in BC and other cancers. 38-44 NCKAP5 , potentially functioning in microtubule bundle formation and microtubule depolymerization, is less studied, and polymorphisms in this gene are reported to be associated with the clinical outcome of gastric cancer patients in a recent study. 45 Overall, our study suggests different genetic factors controlling tumor onset, multiplicity, metastasis, as well as the site of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…PTPRT and ARHGEF4 were identi ed as hub genes in our research. PTPRT, known as a tumor suppressor gene, is implicated in regulating various cellular processes including cell growth, differentiation, mitotic cycle, and oncogenic transformation [40][41][42] . It has been shown to play important roles in promoting malignant cell proliferation in HCC patients harboring hepatitis B virus 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The study of Zhu et al suggested that ARID1A mutations were related to the good prognosis of immune checkpoint inhibitors (ICI) therapy based on the pan-cancer population [ 59 ]. The study of Chen et al suggested that PTPRT mutation is associated with poor progression-free survival in pan-cancer and NSCLC [ 60 ]. Contrary to our results, the study of Zhang et al showed that melanoma patients with PTPRT mutations harbored a significantly elevated ICI response rate and a prolonged survival outcome, and in the NSCLC cohort, the favorable response and immunotherapy survival were also observed in PTPRT -mutated patients [ 61 ].…”
Section: Discussionmentioning
confidence: 99%